SECURE ROUTING IN MANET USING HYBRID CRYPTOGRAPHY - Sivamurugan, D.; Raja, L. (International Journal of Research -GRANTHAALAYAH, 2017)
Mobile ad hoc network (MANET) is a group of mobile nodes that communicates with each other without any supporting infrastructure. These networks have some unique features such as dynamic mobility, open nature, lack of infrastructure, limited physical security and they are vulnerable to several security threats. Malicious node can drop all or partial received packets instead of forwarding them to the next hop through the path. In order to find the malicious nodes, an initial transmission is made between the source and destination nodes. Using fuzzy rules, the trust value of each node is computed and it varies from 0 to 1. A common threshold value is set for each node and by using this threshold value, every node in the network can be identified as either a malicious node or a regular node. After identifying the malicious nodes, these nodes are eliminated by muting the power to off state. As the malicious nodes are eliminated between source and destination nodes, source node can select another trusted path to its destination node. For security and authentication of routing information, hybrid cryptography is employed, using advanced encryption standard (AES) and elliptic curve cryptography (ECC) algorithms. AES algorithm is used as symmetric algorithm to encrypt the routing information and ECC algorithm is used as asymmetric algorithm to encrypt the public key. During encryption, the original plain text is converted into cipher text with encrypted public key and similarly during decryption cipher text is converted into original plain text with decrypted private keys. So the proposed method involves both AES and ECC algorithms which provides security mechanism as efficient and sufficient one. The experimental simulations are carried for the proposed model using network simulator 2 (NS-2) for Throughput, Delay, Packet delivery ratio, Packet overhead and Packet drop.